Effects of dietary fibres extracted from defatted sesame husk, rice bran & flaxseed on hypercholesteromic rats. (January 2019) - Nandi, Isita; Sengupta, Avery; Ghosh, Mahua
Abstract: Sesame, rice bran and linseed, three well known oil seeds, are known to be rich in soluble and insoluble dietary fibres also. Our recent study discovered that the total dietary fiber (TDF) extracted from these defatted oil seeds consist about 68%, 27% and 39% dietary fiber respectively. The cholesterol lowering effect of dietary fiber and polyphenol rich products obtained from other sources are already well studied but these three have not been reported yet. In the present study extraction, functional properties and nutritional evaluation of these three dietary fibres are reported. The in vivo study was conducted with five groups of animals. One group of five adult male Wistar rats were fed a purified cholesterol-free diet for 32 days, the second group was fed with 1 g/100 g cholesterol added diet for 32 days and the other three groups with 1 g/100 g cholesterol-added diets for 32 days, along with 3 g/100 g experimental dietary fibres diet as a source of dietary fiber for the last 28 days. The study shows that extracted TDF from flaxseed, rice bran and sesame husk could lower total cholesterol and triglyceride level in serum and increased the brain and liver phospholipids/cholesterol ratio. HDL-cholesterol concentration was also significantly higher and serum LDL-cholesterol concentrations were significantly lower in rats fed TDF extracted from these oil seeds than the control hypercholesterolemic group These results indicate that the TDF extracted from flaxseed, rice bran and sesame husk reduce serum total cholesterol and LDL-cholesterol, as well as the atherogenic index, in hypercholesterolemic rats. Graphical abstract: fx1